China and Russia in the perception of peruvian university - Donayre, Ramon León (2019)
A sample of 610 university students (265 men and 345 women, between 17 and 29years old) residing in Metropolitan Lima answered a survey about the importanceof the importance of Russia and China for Peru, its status as political and militarypowers in currently and in 2050, as well as their preference for Chinese and Russianproducts. The assessment of China’s importance to Peru was much greater than thatof Russia. Regarding preferences, 56.77% of respondents would be inclined to carryout postgraduate studies in Russia versus 43.22% in China; 54.82% also consideredthat Russia was more important than China in the profession studied; and 55.41%granted more value to a PhD in a Russian university than to one obtained in China(44.59%). Drugs (65.84%), automobiles (63.76%) and Russian toys (54.73%) weremore preferred than Chinese, but, on the contrary, TVs (61.61%), laptops (54.35%) andrefrigerators (52.30%) Chinese obtained higher percentages of preference.